Epicardial ablation utilizing remote magnetic navigation in a patient with Brugada syndrome and inferior early repolarization. Issue 2 (10th October 2017) - Lim, Paul Chun Yih; Nademanee, Koonlawee; Lee, Edward Chun Yi; Teo, Wee Siong
Abstract: We report a case of epicardial ablation in a combined Brugada and inferior early repolarization syndrome patient with recurrent defibrillator therapy for spontaneous ventricular fibrillation. Electroanatomic mapping and ablation were achieved with remote magnetic navigation. Highly fractionated electrograms were seen epicardially in the anterior right ventricular outflow tract (RVOT) and at the anterior‐inferior right ventricle. Ablation of the RVOT region resulted in resolution Brugada pattern electrocardiogram. The inferior early repolarization persisted despite ablation of the inferior right ventricular epicardium. Our patient remained event free at 12‐months follow‐up.